A vocalização da lateral /I/ por analogia da fala de aprendizes da Língua Inglesa - Pasini, Glaucia (2020)
The language is part of a dynamic society, so there is nothing fairer than studying it from its variable character. The great area of sociolinguistics proposes an authentic view of the language, which has a study that embraces the social context and focuses essentially on real rather than ideal speech. Sociolinguistics is also interested in the contact between languages, since it is a natural phenomenon and responsible for producing variations in the linguistic system. When it comes to linguistic variations, it can be said that the West Region of Santa Catarina is very highlighted by the contact between Portuguese the European immigration languages, mainly Italian and German ones. Languages, when in contact, leave characteristics in each other. Therefore, this study focuses on the phonological marks found in the speech of English language students, possibly left from the Italian language, which, in turn, changed to Portuguese within a bilingual setting. Because of this, we seek to analyze the vocalization of the lateral /l/ - a frequent phenomenon in Brazilian Portuguese – in English in the speech of students’ children of Italian-Brazilian descendants in two public schools of middle school (6th and 9th grade) in urban and rural territory of Xanxerê city. The aim was to find out which language (Portuguese or Italian) has the most phonological influence on the English language. The research follows the theoretical line of Multidimensional and Relational Dialectology and its analyzes are based on the following dimensions: diatopic (urban and rural), diagerational (GII [14-year-old students], GI [11-year-old students]), diassexual (male and female), and diaphasic (questionnaire and reading). In the analysis, the data are organized and related based on these dimensions and in a very general way, the results point to a loan of the /l/ vocalized of the Portuguese language replacing the velarized one of English. Another relevant conclusion is that a large part of the informants, mainly those from the rural school, had a low level of knowledge of the English language, which was evidenced by the fact that they use the phonological awareness of Portuguese to pronounce the words in English.